Communication Strategy of Community "Dari Halte ke Halte" To Introduce Indonesian Culinary in the Greater Jakarta Area : A Systematic Literature - Viseria, Bella; Ridaryanthi, Melly (Jurnal Visi Komunikasi, 2025)
Indonesia's culinary delights, rich in unique spices and seasonings from each region, attract domestic and international travelers. This richness reflects a diverse cultural identity in Indonesia, strengthening social interaction and contributing significantly to the tourism economy. In the digital era, social media has emerged as a key platform for promoting culinary ventures, enabling interaction and broad dissemination of information. The culinary community "Dari Halte Ke Halte" employs a unique communication strategy to showcase Indonesian cuisine, particularly in Jakarta. This article conducts a systematic literature review to examine the communication strategy utilized by the community. As an initial phase of ongoing research, the findings aim to provide academic contributions to communication science and practical insights for culinary communities and government institutions in developing effective culinary promotion initiatives. This article analyzes issues, concepts, research focus for future research that has the potential to introduce Indonesian culinary using systematic literature review.